Attitude of upper-grade students of secondary schools towards the humanities - Rajeckas, V. (Psichologija, 1962)
In the communist education, the humanities, such as literature, history, geography, and languages, played a special role. Recently, however, since students’ interest in technology and sciences has significantly increased, the interest in the humanities has diminished to some extent.This article aims to show the attitude of upper-grade students towards the humanities under the new conditions – by combining teaching with production work.The favorite subjects in the 9th grade are history, geography, literature, and languages. In the 10th grade, physics and chemistry rise to the top place.The majority of students consider all taught subjects necessary and useful, although, as they say themselves, they do not always pay necessary attention to the humanities.The most important direct incentive learning motives in upper grades are practical significance of the educational materials and quality of teaching. A bigger or smaller role is also played by the perception of one’s duty as a student, interest in everything that is new and not known yet. Students are fascinated by difficulties at work and overcoming them, success in studies, participation in activity groups, laboratory classes, etc.The majority of upper-grade students understand the significance of languages, literature, history, and geography correctly. They especially appreciate their native and the Russian language (they call it the second mother tongue). The 9th grade students read more fiction works that is diverse topic-wise, whereas the 10th grade students only read the literature indicated in the program.The upper-grade students perceive the significance of the humanities in life very differently. The majority of them think that knowledge acquired when learning the humanities is necessary in public activities, yet are not applicable in production work.Very good and excellent marks in the Lithuanian and Russian languages in writing and foreign language constitute a very small percent. They get much better marks in history and geography.The upper-grade students barely participate in extramural work associated with the humanities and such groups are not numerous in students at the majority of schools.A comparatively small fraction of students desire a profession in the humanities (50 of 601, or 8 %).The most important conclusions of the paper are the following.1. The humanities have a very great importance in the education of members of the communist society. They prepare for life and work equally, as well as other educational subjects.2. The majority of upper-grade students understand the significance of the humanities in the right way; however, they frequently pay insufficient attention to it.3. Teaching the humanities must be associated with life, practice of building communism. Practical significance of the educational material, as well as quality of teaching, are the most important directly incentive motives in upper-grades.4. The interest in the sciences and technology may take place in parallel with the interest in the humanities.5. It is necessary to sum up the newest experience and find out the main ways and forms that would help form a positive attitude towards the humanities and help to enhance an interest in them.
Keywords: the humanities and attitude towards the humanities